Use of secondary somatic embryos improves genetic fidelity of cocoa (Theobroma cacao L.) following cryopreservation - Wetten, Andy; Adugyamfi, R; Fang, J.-Y; Rodriguez-Lopez, C (MTT, 2008)
Because of the recalcitrant nature of cocoa seed and the vulnerability of field collections it is a priority to establish a replicated cryopreserved base collection of existing cocoa germplasm. Thus approximately 600 accessions of cocoa are being cryopreserved at Reading University through the encapsulation-dehydration of floral-derived somatic embryos (SEs) (1). This vitrification-based procedure involves the rapid cooling of the prolific secondary SEs obtained from cultured cotyledonary explants of primary SEs. Analysis of embryogenic development using environmental scanning electron microscopy has revealed that, while primary SEs arise from intermediate callus, secondary SEs are generally initiated directly from epidermal cells. Due to concern about somaclonal variation arising as a result of the protracted callus phase involved in the generation of these propagules, their genetic fidelity has been tested and primary SEs have been found to exhibit a significant mutation frequency (2). In this study nuclear microsatellite-based screening has been applied to each of the cocoa linkage groups in SEs sampled from sequential stages of the cryopreservation procedure (ie following culture, sucrose pretreatment, dehydration over silica and thawing after storage in liquid nitrogen) and compared with profiles for the donor tree. For all 48 regenerants tested in duplicate none exhibited aberrant profiles with respect to the donor tree for any of the 12 microsatellites screened. We conclude that, within the limits of this test population, no gross chromosomal changes occurred during cryopreservation and that, until an efficient means of apical shoot culture is established for cocoa, secondary SEs constitute the best target tissue for cryopreservation of germplasm.
Keywords: Ka; cotoledonary explants; encapsulation-dehydration; somaclonal variation